- #1

- 19

- 0

## Homework Statement

Having shown that:

[tex]f(x) = e^{ax} = \frac{sinh(a\pi)}{\pi}\sum^{\infty}_{n=-\infty}\frac{(-1)^{n}(a+in)}{(a^{2}+n^{2})}e^{inx}[/tex]

on [tex](-\pi,\pi)[/tex] with 'a' a real constant

Deduce that:

[tex]\pi coth(a\pi) = \frac{1}{a} + \sum^{\infty}_{n=1}\frac{2a}{(a^{2}+n^{2})} [/tex]

## Homework Equations

[tex]sinhx = \frac{e^{ax} - e^{-ax}}{2}[/tex]

[tex]coshx = \frac{e^{ax} + e^{-ax}}{2}[/tex]

[tex]cothx = \frac{coshx}{sinhx}[/tex]

## The Attempt at a Solution

I was able to derive the very top equation; I then set [tex]x=\pi[/tex] (in the top equation) so that it reduced to:

[tex]e^{a\pi} = \frac{sinh(a\pi)}{\pi}\sum^{\infty}_{n=-\infty}\frac{(a+in)}{(a^{2}+n^{2})}e^{inx}[/tex]

I know that by fiddling around with the definition of cothx I can get fairly close to what I want, but my major issue here is the change of the 'interval' of summation between what I have shown and what I am aiming to show. Any help would be greatly appreciated.

Last edited: